2019
DOI: 10.1093/ehjcr/ytz188
|View full text |Cite
|
Sign up to set email alerts
|

The use of serial cardiac 18F-fluorodeoxyglucose– positron emission tomography imaging to diagnose, monitor, and tailor treatment of cardiac sarcoidosis patients with arrhythmias: a case series and review

Abstract: Background Clinically evident cardiac involvement has been documented in 5% of sarcoidosis patients, primarily manifesting as heart block, ventricular arrhythmias, and heart failure. Heart Rhythm Society consensus guidelines recommend advanced cardiac imaging with fluorodeoxyglucose–positron emission tomography (FDG-PET) scan for diagnosis of cardiac sarcoidosis, given endomyocardial biopsy’s low sensitivity. Case summary  We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Repeat PET scan allows for assessment of treatment response and can help to adjust immunosuppression. 75,[84][85][86] One study also showed that a reduction in FDG uptake was associated with an increase in LVEF. 87 There are scarce data supporting the use of PET scan for risk stratification in patients with CS although one study showed a significant association between SUV count at the time of diagnosis and future cardiac events.…”
Section: Cmr Vs Nuclear Medicinementioning
confidence: 99%
“…Repeat PET scan allows for assessment of treatment response and can help to adjust immunosuppression. 75,[84][85][86] One study also showed that a reduction in FDG uptake was associated with an increase in LVEF. 87 There are scarce data supporting the use of PET scan for risk stratification in patients with CS although one study showed a significant association between SUV count at the time of diagnosis and future cardiac events.…”
Section: Cmr Vs Nuclear Medicinementioning
confidence: 99%
“…FDG-PET can be used to guide both diagnosis and management of sarcoidosis, 1 2 and may be useful for assessing treatment response, disease extent, occult disease, 3 and may have utility in stratifying prognosis 4 and FDG-PET and cardiac MRI can be complementary, 5 but there is significant radiation exposure associated with repeated PET imaging. Follow-up FDG-PET after 6 months of therapy showed interval reduction in cardiac metabolic activity and improvement in the pulmonary and nodal disease (figures 1B and 2B).…”
mentioning
confidence: 99%